Three-dimensional Natural Combination, Covenant, Fitrah, and Maqasid: Towards the Current Legitimacy of the Science of Jurisprudence - Bouhanneche, Noura (Journal of Contemporary Maqasid Studies, 2024)
The aim of the rise of the science of jurisprudence, fiqh comes together in an instrumental pattern, that assumes the disciplinary formulation of human conduct, thus achieving legal and moral objectives, by which to preserve the moral essence of man. When we analyse the cognitive and methodological context of fiqh, we find out that its systematic structure is revealed through the existence of an authority that guarantees legitimacy. By that, we mean the charter in its communicative and then applied style, which has been ensured qualitatively by Sunnah. Within the framework of the charter, the jurist compares the event which occurs in the existential experience, with the referential law of Sharia, in order to infer a ruling. This has a role in constructing the disciplinary status of human conduct. In fact, it is the same practical process that the moralist launches in the field of applied ethics, within a secular framework, and a rational tool The current condition is subject of a normative confusion that has afflicted humanity with moral and normative deafness, and it is thus similar to what afflicted it at the Tower of Babel, as the lack of understanding has moved from language to moral standards. The implied understanding in knowledge of moral standards has disappeared because nihilism and ambiguity are controlling the existential aspect of humanity. The sign of this referential dispersion and the values disappearance has impelled the quest for a philosophical field, in order to reformulate morality, as the adjacent crisis nowadays is ethical par excellence. Accordingly, philosophy has its role in reviving the ethical concern through examination and investigation. In this context, fiqh as an Islamic account has the merit in moral disciplinary awareness that would re-intensify the shaky looseness of the present morality, and the purposeful reconsideration of the contemporary human condition.